The Role of Premarket Factors in Black-White Wage Differences - Neal, Derek A.; Johnson, William R. (Journal of Political Economy, 1996)
The authors regress young adult wages on current age and the score of a basic skills test that was administered over ten years earlier, when respondents were preparing to leave high school and embark on work careers or postsecondary education. Controlling for this one measure of premarket skill greatly reduces the measured black-white wage gap for young adults. The authors' results suggest that the black-white wage gap primarily reflects a black-white skill gap that exists before young men and women enter the labor market. This skill gap in part reflects measured black-white differences in wealth and family background. Copyright 1996 by University of Chicago Press.